Coarse and Fine Two-stage Fast Adjustment of the Ring Platform for Reactor Coolant Pump Bolt Detection based on Decoupling Parallel Mechanism - Shisen Lin; Lubin Hang; Baojun Zhang; Lusheng Zhou; Xiaobo Huang; Junrong Chen; Ziyu Liu; Pengcheng Zhang (Jixie chuandong)
The ring platform serves as the movement and operating benchmark for the online inspection of the nuclear reactor coolant pump bolts，its rapid and high-precision adjustment is the key to whether the bolt online inspection can proceed successfully. Aiming at the needs of adjusting the position and orientation of the ring platform in the radiation environment，a coarse and fine two-stage high-precision fast adjustment method based on the decoupling parallel mechanism is proposed. The first stage adjustment uses the 6-DOF decoupling parallel mechanism to coarsely adjust the ring platform. The second stage fine adjustment uses the 1T2R and 2T1R decoupling parallel mechanisms corresponding to the two independent position and orientation characteristic subsets to sequentially adjust the levelness and coaxiality of platform. The coarse and fine adjustment decoupled parallel mechanisms are synthesized based on the theory of position and orientation characteristic set. It is proposed that the fixed fulcrum of parallel manipulator can be constructed by means of the sponge-vacuum-device's absorbing on the smooth cylindrical wall of the nuclear pump body. Based on the sponge vacuum device，the parallel mechanism is constructed，which can realize the rapid installation，switching and disassembly of each parallel mechanism. The fast adjustment of coarse and fine two stages based on decoupled parallel mechanism provides new ideas for realizing the rapid and high-precision adjustment of the ring platform in the nuclear radiation environment.